Antioxidant capacity in leaves of pear cultivars during the summer season - A. l. Mishko; N. V. Mozhar; A. V. Klyukina; V. V. Vyalkov (Труды по прикладной ботанике, генетике и селекции)
Background. In field conditions during the summer season, high temperatures, drought and increased levels of UV radiation produce a negative impact on plant growth and development. These stressors are capable of initiating oxidative processes in plant cells, causing an increase in the content of toxic reactive oxygen species. To stop the development of oxidative stress, plants activate their antioxidant enzyme system.   Materials and methods. The study was carried out during the summer season in the southern region of Russia on three pear cultivars: ‘Williams’, ‘Lyuberskaya’, and ‘Flamenco’. The activity of the main enzymatic antioxidants – polyphenol oxidase, superoxide dismutase, catalase; and peroxidase – was assessed in pear leaves.   Results. The data obtained showed variability in the tested cultivars during the studied summer season. The control European cultivar ‘Williams’ had a lower level of enzyme activity in the summer of 2021, compared to the Russian cultivars ‘Lyuberskaya’ and ‘Flamenco’. In 2022, its activity indicators of polyphenol oxidase and superoxide dismutase significantly exceeded the values of cv. ‘Lyuberskaya’ only at the outset of the summer.   Conclusion. According to the results of the study, the pear cultivars showed different levels of enzyme activity during the studied period, and their maximum growth and stable height corresponded to the warmest and driest month. The Russian cultivars demonstrated greater uniformity in the dynamics of their antioxidant activity. compared to the European cultivar ‘Williams’.